2008
DOI: 10.1007/s00198-008-0798-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidants combined to resistance training on BMD in elderly women: a pilot study

Abstract: Antioxidant vitamins may offer some protection against bone loss in the same extent as resistance exercise although combining both does not seem to produce additional effects. Our results suggest to further investigate the impact of antioxidant supplements on the prevention of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 31 publications
3
55
0
1
Order By: Relevance
“…Administration of vitamin C in vivo prevented bone loss with decreased reactive oxygen species [10][11][12]. Some studies of humans also showed that high plasma levels or dietary intake of antioxidants is associated with increased bone mineral density [13][14][15]. In addition, vitamin C is a cofactor in collagen formation and hydroxylation of lysine and proline [16], which are important for bone maintenance [17].…”
Section: Introductionmentioning
confidence: 94%
“…Administration of vitamin C in vivo prevented bone loss with decreased reactive oxygen species [10][11][12]. Some studies of humans also showed that high plasma levels or dietary intake of antioxidants is associated with increased bone mineral density [13][14][15]. In addition, vitamin C is a cofactor in collagen formation and hydroxylation of lysine and proline [16], which are important for bone maintenance [17].…”
Section: Introductionmentioning
confidence: 94%
“…Follow-up interviews indicated no major changes in lifestyle. Results suggest that the benefits of a physical activity and nutrition intervention program can be maintained 6 months later when exercise continues for at least 30 minutes 3 days per week.EFFECT OF ANTIOXIDANTS COMBINED WITH RESISTANCE TRAINING ON BMDIN ELDERLY WOMEN: A PILOT STUDY(41) In a positive quality 6-month study, Chuin and colleagues(41)compared the effects of antioxidant supplementation and resistance training on 278 M. F. Kuczmarski et al…”
mentioning
confidence: 98%
“…At 100 mg of α-tocopherol together with 500 mg vitamin C, and combined with aerobic training in a group of healthy elderly participants, there was no effect on bone resorption markers, but a decrease in bone formation markers [39]. Higher doses (600 mg α-tocopherol and 1000 mg/day vitamin C) coupled with resistance training in post-menopausal women prevented LS BMD loss [40].…”
Section: Discussionmentioning
confidence: 96%